Laboratory Parameters Suggesting a Potential Diagnosis of COVID-19 - SAnchez, Naivy; Rodríguez, Iliana; Lorenzo-Luaces, Patricia; Valenzuela, Carmen; Sanchez, Lizet; Crombet, Tania; Mazorra, Zaima; Hidalgo, Carlos; Saavedra, Danay (Archives of Clinical and Medical Case Reports, 2022)
COVID-19 presents with a broad clinical spectrum. In symptomatic patients, the clinical manifestations could be similar with those observed in other respiratory tract infections. Hematological and biochemical parameters are different between patients with COVID-19 disease and non- COVID-19 patients. To recognize which laboratory parameter could be useful for identifying COVID-19 patients, we applied receiver operator characteristic curves, logistic regression and represented a nomogram. We found that the number of white blood cells (WBC), lymphocytes and neutrophils were significantly lower in COVID-19 than in non-COVID-19 patients, whereas platelets to lymphocyte ratio, Gamma-Glutamyl Transferase (GGT) and creatinine were higher in COVID-19 patients. Based on receiver operating characteristic curves and logistic regression were selected lymphocytes <1.95 x109/L, GGT>46.5 U/L and WBC <6.6 x109/L for predicting the presence of COVID- 19. The use of the nomogram as a practical application can predict the presence of COVID-19 among the symptomatic patients.